LAW PREPAREDNESS AND ENFORCEMENT FOR AIRBORNE AND DROPLET-BORNE INFECTIOUS DISEASES IN INDUSTRIES: A SYSTEMATIC REVIEW - Yasin, Siti Munira; Taib, Khairul Mizan; Samsudin, Ely Zarina; Isa, Mohamad Rodi; Abdullah, Nik Nairan; Ruslan, Nur Hasanah; Yasin, Nurul Ibtisyami; Nozmi, Noramira; Anuar, Mohd Ridzuan; Hair, Ahmad Fitri Abdullah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
Airborne and droplet-borne infectious diseases are a significant risk to industrial workers, where they communicate and work in the same contained areas or share equipment. The workers’ interactions in industrial workplace settings may expose them to infectious diseases, such as influenza and COVID-19. This research aims to identify the laws and enforcement related to communicable diseases that involve airborne and droplet transmission, thereby enhancing preparedness. A systematic review was conducted via Scopus, four biomedical electronic databases (PubMed, Scopus, Web of Science, and Cochrane Library), and three occupational safety and health electronic databases (OSHLINE, NIOSHTIC2 and HSELINE). A total of 25 studies were included, of which 17 studies focused on law preparedness, one study focused on law enforcement, whereas seven studies included both law preparedness and enforcement. The majority of the study designs employed cross-sectional studies (n = 15), with qualitative studies (n = 5), a mixed-methods study (n = 1), a cohort study (n = 2), a case-control study (n = 1), and a case study (n = 1). Studies on preparedness measures emphasise environmental interventions (e.g., traffic control, cleaning, and supply chain management), administrative actions (e.g., limiting visitors, regular disease screening, adequate personal protective equipment, training, and education), and comprehensive preparedness guidelines.